2013
DOI: 10.1111/bjep.12022
|View full text |Cite
|
Sign up to set email alerts
|

Improving reading comprehension in reading and listening settings: The effect of two training programmes focusing on metacognition and working memory

Abstract: Our study suggests that activities focusing specifically on metacognition and WM could foster text comprehension, but the potential benefit is influenced by the training modality, that is, the Reading group obtained greater and longer-lasting improvements than the Active control or Listening groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
60
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 46 publications
15
60
1
5
Order By: Relevance
“…These results are consistent with previous findings collected by García-Madruga et al (2013) and are in line with a compensation effect identified in other training studies (e.g., Carretti et al 2014;Cornoldi et al 2015). The negative correlations between baseline cognitive performance and training gains could stem from the fact that the procedure used in our training program promoted a better executive control of processes implicated in WM and reading comprehension, rather than inducing participants to use particular strategies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are consistent with previous findings collected by García-Madruga et al (2013) and are in line with a compensation effect identified in other training studies (e.g., Carretti et al 2014;Cornoldi et al 2015). The negative correlations between baseline cognitive performance and training gains could stem from the fact that the procedure used in our training program promoted a better executive control of processes implicated in WM and reading comprehension, rather than inducing participants to use particular strategies.…”
Section: Discussionsupporting
confidence: 92%
“…WM training in children have had some effect in improving or sustaining reading comprehension (Henry et al 2014). There is also some preliminary evidence of training involving WM processes having positive effects on children's-without reading comprehension or WM difficulties-reading comprehension at school (e.g., García-Madruga et al 2013;Carretti et al 2014), sustaining the importance of these interventions in improving such a crucial ability. The originality of these studies lies in that the training activities were proposed in the classroom, as part of normal school activities.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A ocorrência de déficits na compreensão leitora em indivíduos diagnosticados com Distúrbio de Aprendizagem é amplamente apontada na literatura e, desta forma, merece atenção especial (SILVER et al, 2008;WU;HUAN;MENG, 2008;PINHEIRO;MACHADO;OLIVEIRA;CAPELLINI, 2012 JERMAN, 2007;SESMA et. al., 2009;FARIA;JÚNIOR, 2012;BOTTINO;PICCOLLO;CARRETTI et al, 2014;SCHROEDER, 2014 A habilidade cognitiva de memória de trabalho fonológica foi a que mais se destacou dentre as habilidades testadas. Foi à única que evidenciou diferença estatística na comparação entre os grupos experimentais, com melhor desempenho do GE2.…”
Section: Comparação Do Desempenho Nas Habilidades Testadas De Criançaunclassified